Reaching Sustainable Development Goals: An Examination of Climate Change’s Impact and Green Intellectual Capital, Competitive Business Strategy as a Moderating Variable: English - Hendar Muhammad Rifoaffa; Susi Dwi Mulyani (Cita Konsultindo Research Center, 2024)
The phenomenon of primary and company management attempts to reduce energy use and pollution is the basis for this paper's preparation. It follows that a green economy theme will undoubtedly be incorporated into the manufacturing sector's transformation model in the future. This is because businesses need to be able to manage how they use their resources and assets in order to maintain sustainable company continuity. The manufacturing sector and the adoption of the green economy are strongly correlated in this study, giving researchers the creative opportunity to use the sustainable development goals as achievement points and the phenomena of GIC and climate change as a supplementary variables toward the accomplishments in this paper into practice. This study presents findings about the phenomenon of the manufacturing sector attempting to apply green economic mechanisms. The data gathered has clarified the relationship between CC and SDG’s, in addition to the advantages of GHC, GSC, GRC, and total assets. Additionally, CBS can bolster the impact of GHC and GRC on sustainable development goals. To increase the success and sustainability of manufacturing industry businesses, all types of stakeholders concentrate on changes in competitiveness and the managerial implications of the green economy. However, they also ensure sustainability in key mechanisms and features to enable them to meet the demands and challenges of changing era. In order to address changes in the competitive environment among manufacturing industries, where process opportunities are abundant for companies to manage competitive climate risk issues so that their implementation will enhance the welfare of stakeholders and society as a whole, this paper will develop a sustainable value approach.